Examining the psychological and social impact of relative age in primary school children: a cross‐sectional survey. (25th May 2017) - Price, A.; Allen, K.; Ukoumunne, O. C.; Hayes, R.; Ford, T.
Summary: Background: A number of studies demonstrate that children who are younger within their school year have poorer academic attainment and are more likely to have special educational needs. Few, however, have considered the impact relative age may have on child mental health, behaviour and happiness in school. Methods: This paper utilized data from the Supporting Teachers and Children in Schools study (2075 pupils aged 5 to 9 years from 80 primary schools) to explore the relationship among relative age, behaviour and happiness in school. Behavioural and emotional development was assessed by using the teacher‐reported and parent‐reported Strengths and Difficulties Questionnaire and the Pupil Behaviour Questionnaire. Children's happiness within school was assessed by using the How I Feel About My School Questionnaire. Results: Relatively younger children had higher Total Difficulties scores on the Strengths and Difficulties Questionnaire than their peers. There was a mean increase per 30‐day decrease in relative age of 0.09 (95% CI: 0.03 to 0.16; p  = 0.007) in teacher‐reported and 0.08 (0.001 to 0.16; p  = 0.05) in parent‐reported scores. There was little evidence of a relationship between relative age and children's behaviour and happiness in school. Conclusions: For children with complex difficulties, being relatively young for their school year may be an additional stressor that may undermine mental health.